On the integrability of money-demand functions by the Sidrauski and the shopping-time models - Cysne, Rubens Penha; Turchick, David (Journal of Banking & Finance, 2009)
This paper investigates which properties money-demand functions must satisfy so that they are consistent with Lucas’s [Lucas Jr., R.E., 2000. Inflation and welfare. Econometrica 68, 247–274] versions of the Sidrauski and the shopping-time models. We conclude that shopping-time-integrable money-demand functions are necessarily also Sidrauski-integrable, but that the converse is not necessarily true, unless a boundedness assumption on the nominal interest rate is made. Both the log–log with an interest-rate elasticity greater than or equal to one and the semi-log money demands may serve as counterexamples. All the models and results are also extended to the case in which there are several assets in the economy performing monetary functions.